Growth Performance, Meat Quality and Antioxidant Status of Sheep Supplemented with Tannins: A Meta-Analysis - José Felipe Orzuna-Orzuna (MDPI AG, 2021)
The objective of this study was to evaluate the effects of dietary supplementation with tannins (TANs) on productive performance, carcass characteristics, meat quality, oxidative stability, and blood serum antioxidant capacity of sheep through a meta-analysis. Using Scopus, Web of Science, ScienceDirect, and PubMed databases, a systematic search was performed for studies published in scientific journals that investigated the effects of TANs supplementation on the variables of interest. Only studies with weaned or older sheep were included. The data analyzed were extracted from 53 peer-reviewed publications. The sheep included in the present study were between 2 and 6 months old, and between 12 and 31 kg of body weight. The effects of TANs were analyzed using random-effects statistical models to examine the standardized mean difference (SMD) between treatments with TANs and control (no TANs). Heterogeneity was explored by meta-regression and a subgroup analysis was performed for covariates that were significant. Supplementation with TANs did not affect dry matter intake, pH, color (L* and b*), Warner–Bratzler shear force, cooking loss and meat chemical composition (p > 0.05). Supplementation with TANs increased daily weight gain (SMD = 0.274, p < 0.05), total antioxidant capacity (SMD = 1.120, p < 0.001), glutathione peroxidase enzyme activity (SMD = 0.801, p < 0.001) and catalase (SMD = 0.848, p < 0.001), and decreased malondialdehyde (MDA) concentration in blood serum (SMD = −0.535, p < 0.05). Supplementation with TANs decreased feed conversion rate (SMD = −0.246, p < 0.05), and the concentration of MDA (SMD = −2.020, p < 0.001) and metmyoglobin (SMD = −0.482, p < 0.05) in meat. However, meat redness (SMD = 0.365), hot carcass yield (SMD = 0.234), cold carcass yield (SMD = 0.510), backfat thickness (SMD = 0.565) and the Longissimus dorsi muscle area (SMD = 0.413) increased in response to TANs supplementation (p < 0.05). In conclusion, the addition of tannins in sheep diets improves productive performance, antioxidant status in blood serum, oxidative stability of meat and some other characteristics related to meat and carcass quality.